1998
DOI: 10.3171/jns.1998.88.3.0506
|View full text |Cite
|
Sign up to set email alerts
|

Neurotopographic considerations in the microsurgical treatment of small acoustic neurinomas

Abstract: Hearing preservation postsurgery by tumor type was as follows: 1A, 92%; 1B, 88%; 1C, 100%; 2A, 83%; 2B, 92%; and 3, 57%. Combined, this represents a hearing preservation rate of 87% after surgical treatment of Grade II acoustic neurinomas. Full nerve function was maintained in 88% of patients with anatomically preserved facial nerves in both Grade I and II tumors. The remaining 12% of patients retained partial function of the facial nerve. Two patients in the series lost anatomical integrity of the nerve due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
157
2
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(187 citation statements)
references
References 46 publications
(18 reference statements)
1
157
2
13
Order By: Relevance
“…The mean age was 47.5 years (range, 17-76 years), and the mean tumor volume was 1353 mm 3 (range, 64-4640 mm 3 ). According to the Koos classification (17), the lesion treated was Stage I in 8 cases, Stage II in 21 cases, Stage III in 43 cases, and Stage IV in 2 cases. The initial symptom was hearing decrease in 29 patients, tinnitus in 22 patients, unsteadiness in 9 patients, and vertigo in 4 patients.…”
mentioning
confidence: 99%
“…The mean age was 47.5 years (range, 17-76 years), and the mean tumor volume was 1353 mm 3 (range, 64-4640 mm 3 ). According to the Koos classification (17), the lesion treated was Stage I in 8 cases, Stage II in 21 cases, Stage III in 43 cases, and Stage IV in 2 cases. The initial symptom was hearing decrease in 29 patients, tinnitus in 22 patients, unsteadiness in 9 patients, and vertigo in 4 patients.…”
mentioning
confidence: 99%
“…2,12 Microsurgery is the first option if the tumor is large or symptoms of mass effect and hydrocephalus are present. 4,21,35,36 SRS is generally used to treat small-to medium-sized VSs but has also demonstrated satisfactory results with larger lesions as well. 20,30,31,[39][40][41]45 Nevertheless, the latter represent a challenge for both surgeons and radiosurgeons, because a direct correlation between tumor size and facial nerve damage does exist in the postoperative period.…”
mentioning
confidence: 99%
“…All tumors were Grade 4 according to the Koos classification. 21 Volumes were calculated using the MultiPlan (Accuray) planning system during treatment or using the treatment planning records; on MR or CT images, the formula (D1 × D2 × D3)/2 was adopted, where D1 was the major anteroposterior axis parallel to the petrous bone, D2 was the major axis orthogonal to D1, and D3 was the major craniocaudal axis.…”
mentioning
confidence: 99%
“…Koos et al 50 reported remarkable results in their group of patients with small VSs treated by microsurgery. Good hearing (using the 50/50 rule) was maintained in 100% of patients with Koos Stage 1 tumors and in 87% of patients with Koos Stage 2 tumors.…”
Section: Chances Of Hearing Preservation After Srsmentioning
confidence: 97%